Implications of Historical Trends in the Electrical Efficiency of Computing - Koomey, Jonathan; Berard, Stephen; Sanchez, Marla; Wong, Henry (IEEE annals of the history of computing, 2011)
The electrical efficiency of computation has doubled roughly every year and a half for more than six decades, a pace of change comparable to that for computer performance and electrical efficiency in the microprocessor era. These efficiency improvements enabled the creation of laptops, smart phones, wireless sensors, and other mobile computing devices, with many more such innovations yet to come. The Web Extra appendix outlines the data and methods used in this study.